Implementasi Akuntansi Dana Desa di Desa Banjaragung Kecamatan Bareng Kabupaten Jombang - Diana Kholidah; Deasy Ervina (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2021)
Village Fund Accounting, namely the recording of transactions carried out by the village, both income and expenditure transactions, as evidenced by notes.Villages use Village Fund Accounting in the process of recording their financial statements.The object of this research is in Banjaragung Village, Bareng District, Jombang Regency.This research is a qualitative descriptive study by describing the financial reports in Banjaragung Village.Data analysis techniques by collecting data, data reduction and then drawing conclusions.The results of the study, the financial system used by the village in preparing financial reports uses Siskeudes and uses a cash basis, Banjaragung Village also uses Village Fund Accounting in the process of recording village financial reports consisting of cash books, bank books, tax books, APBDesa and budget realization reports, so that with the five reports, Banjaragung Village is in the process of recording financial statements in accordance with SAPDesa which contains transparency and accountability. Keywords :Transparent; Accountability; Village Fund Accounting.